1995
DOI: 10.1523/jneurosci.15-11-07612.1995
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic changes in locomotor behavior and in expression of mRNA for NGFI-A and NGFI-B in rat striatum following acute caffeine administration

Abstract: The time course of expression of mRNA for NGFI-A and NGFI-B after a single intraperitoneal injection of saline or caffeine was examined using in situ hybridization. Administration of a high dose of caffeine (100 mg/kg) decreased locomotor behavior and increased NGFI-A and NGFI- B mRNA in the entire striatum. A lower dose of caffeine (50 mg/kg) caused a weak enhancement of both messages, which was confined to the lateral part of caudate-putamen. This dose increased horizontal, but not vertical, movement. In rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0
5

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 67 publications
8
65
0
5
Order By: Relevance
“…Conversely, the D 2 agonist effect on c-fos in D 1 -containing neurons might be related to activation of presynaptic D 2 autoreceptors located on dopaminergic terminals, because this strongly decreases striatal dopamine release (Imperato et al, 1988;Suaud-Chagny et al, 1991) and thereby the D 1 -mediated activity in striatonigral neurons. Decreases of mRNA coding for the immediate early gene NGFI-A (zif 268) have been described after treatment with drugs acting on D 2 or A 2A receptors (Gerfen et al, 1995;Svenningsson et al, 1995), but we describe here for the first time the D 2 -mediated inhibition of c-fos expression in the two striatal output neurons.…”
Section: Effect Of D 2 and D 1 Agonists Given Alone On C-fos Expressimentioning
confidence: 85%
“…Conversely, the D 2 agonist effect on c-fos in D 1 -containing neurons might be related to activation of presynaptic D 2 autoreceptors located on dopaminergic terminals, because this strongly decreases striatal dopamine release (Imperato et al, 1988;Suaud-Chagny et al, 1991) and thereby the D 1 -mediated activity in striatonigral neurons. Decreases of mRNA coding for the immediate early gene NGFI-A (zif 268) have been described after treatment with drugs acting on D 2 or A 2A receptors (Gerfen et al, 1995;Svenningsson et al, 1995), but we describe here for the first time the D 2 -mediated inhibition of c-fos expression in the two striatal output neurons.…”
Section: Effect Of D 2 and D 1 Agonists Given Alone On C-fos Expressimentioning
confidence: 85%
“…The higher corticosterone and ACTH release induced by the 10 mg/kg caffeine dose, especially in the background (60 dB) noise condition is likely a reflection of the ability of caffeine at this dose to induce HPA axis activation basally, as shown in Experiment 3, but not by reducing the threshold to stressful events. A number of prior results suggested that a low dose of caffeine may produce an attenuation of the HPA axis response to stressful stimuli: first, because of the biphasic effects of caffeine reported in some responses (Svenningsson et al, 1995;Garrett and Holtzman, 1995); second, the finding that a similar low dose (2 mg/kg) attenuated the restraint-induced elevations in hippocampal serotonin and dopamine release (Yamato et al, 2002), despite the fact that caffeine alone elevated these neurotransmitters in the hippocampus (Carter et al, 1995); and finally, the existence of a putative mechanism whereby antagonism at adenosine A2a receptors might produce different effects than antagonism at the A1 receptors (Fredholm et al, 1999), as indicated by the findings that only high doses of caffeine (10 mg/kg and above) induce anxiety in rodents (Lister, 1987;Baldwin et al, 1989;Jain et al, 1995;Bhattacharya et al, 1997), while selective blockade of A1 receptors (Florio et al, 1998) but not A2a receptors (El Yacoubi et al, 2000) was reported to induce anxiety. These central actions of caffeine might have been expected to generalize to regulation of the hypothalamic paraventricular nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in rats, caffeine has biphasic effects on locomotor activity (Svenningsson et al, 1995) and rotation behavior (Garrett and Holtzman, 1995), with low doses displaying an activating effect and high doses producing inhibitory effects. Additional evidence also suggests that caffeine may produce biphasic effects related to stress and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, with low caffeine doses (25 mg͞kg or lower) in wild-type animals, it has been hypothesized that A 2A receptors instead of A 1 receptors are preferentially blocked, and hyperlocomotion is induced by net elevation of efficacy of D 2 receptor signaling and depression in G olf activity in striatopallidal neurons (17,23). Higher caffeine doses (75-100 mg͞kg) elicit different responses that involve other pharmacological targets in addition to adenosine receptors, and these higher doses induce striatal immediate-early gene expression (23)(24)(25)(26)(27)(28)(29)(30). Finally, the effects of caffeine in mutants were only marginally inhibited by a combination of dopamine receptor antagonists that substantially reduced L-dopa-activated locomotor activity and feeding, suggesting that most of caffeine's effects are not mediated by release of residual dopamine.…”
Section: Discussionmentioning
confidence: 99%